Efficiency Versus Tax Collection Effectiveness. the Royal Treasury of Chile at the End of the Colonial Period: Dynamics, Formation and Amendments - Martinez-Barraza, J (UNIV CATOLICA NORTE, Inst Invest Arqueologicas y Museo RP Gustavo Le Paige, 2024)
Despite consensus in specialized historiography regarding the swelling of the Spanish Royal Indian Treasuries in the late colonial period, the evidence to support the claim has generally been total tax revenues. In other words, it is based only on collection effectiveness, not efficiency, which would also account for fiscal performance and the ratios between net tax proceeds, collection cost and tax revenue. This paper addresses this deficit in Spanish-American history, evaluating collection efficiency through a case study of the Royal Treasury of Chile from the last third of the 18th century through the colonial decline. Researchers use official documentation on the Chilean treasury s financial position, prepared since the 1780s, to reproduce the actual flow of tax variables. When combined with an examination of the treasury s governance and administration, the analysis demonstrates that, while successful in terms of collection, tax reforms faced serious application and adaptation issues on Chilean soil. Following a costly bureaucratic consolidation process culminating in Intendent-issued ordinances, the abovementioned issues forced local authorities to amend several "modernizing" measures to relieve local financial tensions. These were in place until the colonial decline.